THE EFFICIENCY OF PROTEIN UTILIZATION IN DIFFERENT BROILER STRAINS - Indarsih, B.; Pym, R.A.E. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
The objective of this work was to study the protein utilization and protein turnover of different broilerstrains and was carried out in completely randomized design. One hundred and forty four sexed doc fromeach strain (Cobb =A, Ingham = B and Steggels = C) were divided into a factorial arrangement (threedietary protein, two sexes and three strains). Two regimens of composite mixes of a summit and dilution dietand a free choice between these two diets. Diets were changed weekly, with notional crude protein levelsat one day-old of 240g/kg for all chickens, and at 42 days of age of 120 or 180 g/kg in the low and highprotein. Protein utilization efficiency (PRE) was measured from 39-42 d of age. PRE increased with theincreasing of dietary protein in strains A and C and had much higher response than in strain B. The moisture:protein ratios were 2.51, 2.65 and 2.58 in strains A, B and C, indicating strain B contained higher moistureand body fat and less protein. Involvement of genetic controls as the selection effect seems to increase thecapacity of chickens in improving nutrient utilization